2007
DOI: 10.1002/chem.200601035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Solution Thermodynamics, and X‐ray Study of CuII [12]Metallacrown‐4 with GABA Hydroxamic Acid: An Unprecedented Crystal Structure of a [12]MC‐4 with a γ‐Aminohydroxamate

Abstract: The solution equilibria of gamma-aminobutanehydroxamic acid (GABAha) with H+ and Cu2+ were investigated by potentiometry, titration calorimetry, spectrophotometry, NMR spectroscopy, and ESI-MS. The thermodynamic parameters of the CuII [12]metallacrown-4 obtained for GABAha were compared with those of the corresponding complexes of (S)-alpha-Alaha and beta-Alaha. The stability (-DeltaG0) sequence was beta-Alaha>>alpha-Alaha>GABAha, whereas the order of formation enthalpies (-DeltaH0) was beta-Alaha>>GABAha>alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…A 12-MC-4 can be constructed, by replacing two methylene groups of each macrocycle arm with -M-N-coordination units; in other words, the analogy between the structures of 12-metallacrown-4 and 12-crown-4 is such that both molecules consist of 12-membered macrocycle which offers four oxygen atoms as donors to an ion which can bind in the center of macrocyclic cavity. 12 The sizes of such cavities are similar to each other, although the C-C and C-O and also the M-O and M-N bond lengths are different. It is also worthy to notice that metallacrowns are much more effective in binding a transition metal ion when compared to their organic equivalents, because their oxime oxygen atoms are better donors than the neutral ether oxygen present in the crowns.…”
Section: Introductionmentioning
confidence: 79%
“…A 12-MC-4 can be constructed, by replacing two methylene groups of each macrocycle arm with -M-N-coordination units; in other words, the analogy between the structures of 12-metallacrown-4 and 12-crown-4 is such that both molecules consist of 12-membered macrocycle which offers four oxygen atoms as donors to an ion which can bind in the center of macrocyclic cavity. 12 The sizes of such cavities are similar to each other, although the C-C and C-O and also the M-O and M-N bond lengths are different. It is also worthy to notice that metallacrowns are much more effective in binding a transition metal ion when compared to their organic equivalents, because their oxime oxygen atoms are better donors than the neutral ether oxygen present in the crowns.…”
Section: Introductionmentioning
confidence: 79%
“…β, or γ-hydroxamate ligands were reported earlier. 45,47,48 It was shown that both enthalpic and entropic terms are favourable to the pentameric species formation, although the entropic contributions are always higher, than the enthalpic terms, which are negative in all reported cases. 45,47,48 However, the ΔH value of Cu(II)-PAHEt 12-MC-4 formation is positive indicating that the process is endothermic.…”
Section: Protonation and Complex Formation Equilibria In Aqueous Solumentioning
confidence: 91%
“…45,47,48 It was shown that both enthalpic and entropic terms are favourable to the pentameric species formation, although the entropic contributions are always higher, than the enthalpic terms, which are negative in all reported cases. 45,47,48 However, the ΔH value of Cu(II)-PAHEt 12-MC-4 formation is positive indicating that the process is endothermic. It should be mentioned, that the overall energetic effect of the complexation consists of the dehydratation of the metal cation and the ligand, ΔH dehyd >0, the formation of new metal-ligand bonds ΔH bind <0, as well as dissociation of the metal ion from the buffer.…”
Section: Protonation and Complex Formation Equilibria In Aqueous Solumentioning
confidence: 91%
“…A survey of the Cambridge Structural Database (CSD version 5.41, update March 2020;Groom et al, 2016) reveals that there are 35 different structures; however, even more Cu 5 12-MC-4 complexes have been studied in solution to understand the thermodynamic properties of their self-assembly (Mezei et al, 2007;Tegoni & Remelli, 2012;Ostrowska et al, 2016). Initially Cu 5 12-MC-4 complexes were only produced with ligands that could form fused five-and six-membered chelate rings such as salicylhydroxamic acid or -aminohydroxamic acids (Orama et al, 1992;Gibney et al, 1994;Halfen et al, 1998); however, it is now recognized thatand -aminohydroxamic acids can form Cu 5 12-MC-4 complexes that have fused five-and fivemembered chelate rings or fused five-and seven-membered chelate rings, respectively (Dallavalle et al, 2001;Tegoni et al, 2004Tegoni et al, , 2007Tegoni et al, , 2008. Pentacopper(II) 12-MC-4 complexes have applications as templates for the assembly of peptide bundles (Cal et al, 2013), for the sorption of gases and alcohols (Atzeri et al, 2016;Pavlishchuk et al, 2017), and as building blocks for one-, two-, and three-dimensional materials (Bodwin & Pecoraro, 2000;Gumienna-Kontecka et al, 2007;Lago et al, 2011;McDonald et al, 2013;Atzeri et al, 2016).…”
Section: Chemical Contextmentioning
confidence: 99%